Complication of dislodged gastrostomy Foley catheter: antegrade migration into small bowel. Issue 1 (18th December 2018) - Cmorej, Peter; Barbat, Selwan; Sugawa, Choichi
Abstract : A 65-year-old man with dysphagia underwent placement of a percutaneous endoscopic gastrostomy tube. He was cared for at a nursing facility where the tube became dislodged and was replaced with similar size Foley catheter. Patient was brought to the hospital with dislodged feeding Foley but none was found at the bedside. Diagnostic workup revealed antegrade migration of the catheter into the small bowel. Push enteroscopy was unsuccessful in retrieving the catheter because it was too far distal. Patient was observed for a total of 7 days. Due to lack of progress with conservative measures, a colonoscopy was performed to extract the catheter, thus avoiding the need for more invasive surgical measures. If a Foley catheter is used as a gastrostomy tube, it should be replaced with a dedicated feeding tube as quickly as possible and should always be affixed to the skin to prevent antegrade migration and associated complications.